Characterization of essential oil compounds on leaves and rhizomes of turmeric (Curcuma domestica Val.) - Euis Yuliani; Desi Ratna Sari; Dedi Kurnia; Dinar Rahayu; Siti Nur Inayah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aimed to determine the characterization of essential oils in turmeric leaves and rhizomes using Chromatography-Mass Spectrophotometry (GC-MS). In this study, essential oils were obtained by steam distillation on the leaves and rhizomes of turmeric seven months old in the Panjalu area. Based on the research results, there were eight similar compounds, alpha-phellandrene, 1,3-cyclohexadiene 1-methyl-4-(1-methyl ethyl), P-Cymene, D-Lymonene, Eucalyptol, aR-Tumerone, Tumerone, and Curlone.